Community-Based Assessment of Knowledge, Attitudes, and Practices Towards COVID-19: an Epidemiological Survey in Kurdistan Region, Iraq - Rawf Ali, Zhino; Sharif, Bayan Omar; Amin Kamali, Aram Salih Mohammed; Tofiq Abbas, Varin; Karim Ahmed, Azad; Osman Mahmood, Shaho; Jamal ahmed, Chiman; Ahmed Abdulqader, Sarwat (Kurdistan Journal of Applied Research, 2020)
Covid-19 considered as a pandemic disease and spread very rapidly, the people are needed to respond to this danger situation without becoming complacent because still there is no vaccine for it. The sample of this cross - sectional descriptive study was consisted of 1250 Kurdish male and female, their ages ranged between 14- 76 years. The main objective of the study is conducted to assess the people’s knowledge, attitude, and practice (KAP study) toward COVID-19. The data were collected during the period of April 4 up to June 2020. A self- constructed questionnaire was used for data collection and it was designed according guidelines, literatures, and articles concerning COVID-19; which consisted of 40 variables. The researchers made google form for the questionnaire and distributed by local residents of Kurdistan region. Relying on the authors’ networks, and sent by (Facebook, Instagram, WhatsApp, and Telegram). Therefore, the data analyzed through the using of the (SPSS, version 23). A p value of ? 0.05 was considered statistically significant. The findings of the current study concluded that the main way for obtaining knowledge of the participants was social media and it was much more than ministry of health, WHO and CDC together. Also, the study indicated that the age group of 21-30 years old has a high score of knowledge and attitude while the age group of 31-40 years old has a high score of practical issues regarding COVID-19. As well as, the female employer by Bachelor degree with barely sufficient financial status in urban area had a high score of KAP concerning COVID-19, lastly the present study observed a strong positive correlation between KAP toward coronavirus among the participants. The study recommended to ministry of health and health sectors to present much more scientific healthy issues to improve the knowledge, attitude, and practice of the Kurdish citizens concerning coronavirus because the health care workers are much more dependable scientifically than social media toward COVID-19 to prevent rapid transmission and control this serious situation.